Moderasi Beragama Dan Pluralitas Penafsiran Islam - Mujid; Muhammad Faisal (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2026)
This article examines the relationship between religious moderation and the plurality of Islamic interpretations through hermeneutical analysis of contemporary Islamic discourse. Religious moderation, promoted as the official paradigm of religiosity in Indonesia, faces fundamental epistemological and hermeneutical challenges when confronted with the reality of pluralistic interpretations of religious texts. Through hermeneutical-critical analysis integrating the thoughts of Fazlur Rahman, Khaled Abou El Fadl, and Nasr Hamid Abu Zayd, this study develops a five-dimensional framework encompassing textual-hermeneutical, contextual-historical, ethical-normative, social-dialogical, and institutional-structural dimensions as the foundation for religious moderation based on interpretive plurality. Furthermore, this research formulates a four-phase transformative model comprising deconstruction of interpretive authoritarianism, hermeneutical reorientation, dialogical-integrative engagement, and institutionalization of wasatiyyah to guide the formation of moderate and inclusive Islamic discourse. The findings identify four critical risks, namely interpretive trivialization, hermeneutical relativism, institutional co-optation, and neo-essentialism, which potentially impede the realization of authentic religious moderation